2023
DOI: 10.34067/kid.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Managing Phosphate Burden in Patients Receiving Dialysis: Beyond Phosphate Binders and Diet

Kamyar Kalantar-Zadeh,
Derek Forfang,
George Bakris
et al.

Abstract: Most patients receiving dialysis rely on dietary restriction and phosphate binders to minimize the risk of hyperphosphatemia, which is associated with increased mortality. However, dietary restriction is difficult due to “hidden” phosphate additives in processed foods and medications. Restriction of dietary phosphate sources such as protein may increase the risk of malnutrition. Phosphate binders, the only pharmacologic option for phosphate management since aluminum salts were introduced several decades ago, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It has been observed that the limited intracellular proton retention induced by NHE3 inhibitors leads to a pH-related conformational change in specific tight junction proteins, named claudins, with resulting reduction in the transepithelial permeability to phosphate and then decrease in phosphate absorption. 59,60 Based on these mechanisms, growing evidence is accruing on promising pharmacological agents able to interfere with phosphate absorption, targeting one of the two described pathways rather than bind dietary phosphate in the gastrointestinal tract.…”
Section: New Treatment Paradigms In the Management Of Hyperphosphatae...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the limited intracellular proton retention induced by NHE3 inhibitors leads to a pH-related conformational change in specific tight junction proteins, named claudins, with resulting reduction in the transepithelial permeability to phosphate and then decrease in phosphate absorption. 59,60 Based on these mechanisms, growing evidence is accruing on promising pharmacological agents able to interfere with phosphate absorption, targeting one of the two described pathways rather than bind dietary phosphate in the gastrointestinal tract.…”
Section: New Treatment Paradigms In the Management Of Hyperphosphatae...mentioning
confidence: 99%
“…Active transcellular transport is mediated by specific transporters such as the sodium-dependent phosphate 2b transport protein (NaPi2b), whose expression is regulated by serum phosphorus values through modifications in activated vitamin D3 levels, or type-III inorganic phosphate (Pi) transporters PiT-1 and PiT-2. 58 , 59 Conversely, passive paracellular transport occurs through tight junction complexes along the concentration gradient and involves the sodium/hydrogen exchanger isoform 3 (NHE3). This isoform is largely expressed at the gastrointestinal level where it transports sodium ions into cells in exchange for hydrogen ions, in this way playing a crucial role in maintaining water and acid-base balance homeostasis.…”
Section: New Treatment Paradigms In the Management Of Hyperphosphatae...mentioning
confidence: 99%
See 1 more Smart Citation